Introvert and extrovert personality: Is it correlated with academic achievement of Physical Education, Health and Recreation students at university level? - Hasanuddin Jumareng; Wolter Mongsidi; Edi Setiawan; Ihsan Abdul Patah; Adi Rahadian; Ruslan Abdul Gani (Journal Sport Area, 2021)
Psychological elements, namely introverted and extroverted personalities, are currently one of the keys to determining success in academics at the University level, but it is not clear which type is more correlated with academic achievement. The purpose of this study is to investigate the correlation between introverted and extroverted personalities with student academic achievement. The subjects in this study come from the PJKR Department of the University of Suryakancana (N=20) and Halu Oleo (N=20). Data analysis uses SPSS version 25 to find descriptive statistics, normality, data linearity and person product moment correlation. The level of significance used is 0.05. The results of the study finds that introverted personality is significantly correlated with academic achievement in the high category (r= 0.749**), and extroverted personality is not significantly correlated with academic achievement (r= -0.120). Thus, it can be concluded that the personality of students with introverted type is far superior to extroverts in academic achievement at the University level. The contribution in this study contributes to knowledge in the field of physical education psychology, so that later lecturers can pay more attention and optimize academic achievement in students with both types, especially the extroverted type.